2007
DOI: 10.1088/0741-3335/49/12b/s27
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal and poloidal momentum transport studies in tokamaks

Abstract: This paper reports on recent studies of toroidal and poloidal momentum transport in tokamaks. The ratio of the global energy confinement time to the momentum confinement is found to be close to τ E /τ φ = 1 among several tokamaks. On the other hand, local transport analysis in the core plasma shows a larger scatter in the ratio of the local effective momentum diffusivity to the ion heat diffusivity χ φ,eff / χ i,eff among different tokamaks, for example the value of effective Prandtl number being typically aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 47 publications
3
79
0
Order By: Relevance
“…Early JET intrinsic rotation studies have used this technique [11,23]. The JET intrinsic rotation data included in the multi-machine study of [2] is from XCS measurements from 1994-95, when the wavelength scale had for the first time been calibrated by comparison with the angular frequency derived during NBI from charge exchange recombination spectroscopy of 6 C + . For newer pulses XCS intrinsic rotation measurements are not always available as there isn't enough Ni in the JET machine in X-point plasmas.…”
Section: Iia -Tools For Measuring Intrinsic Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Early JET intrinsic rotation studies have used this technique [11,23]. The JET intrinsic rotation data included in the multi-machine study of [2] is from XCS measurements from 1994-95, when the wavelength scale had for the first time been calibrated by comparison with the angular frequency derived during NBI from charge exchange recombination spectroscopy of 6 C + . For newer pulses XCS intrinsic rotation measurements are not always available as there isn't enough Ni in the JET machine in X-point plasmas.…”
Section: Iia -Tools For Measuring Intrinsic Rotationmentioning
confidence: 99%
“…[4] do not include any contribution from a momentum pinch which is found to exist in JET NBI discharges [6,7] and other tokamaks [8,9]. This inward pinch will modify the rotation profile in ITER, in particular the peaking of the rotation profile will increase.…”
Section: -Introductionmentioning
confidence: 99%
“…Plasmas in NBI heated spherical tokamaks show a fast toroidal rotation with thermal Mach numbers measured on MAST of up to M th = v φ /v th 0.8 [48]. On many tokamaks a link between momentum confinement and energy confinement has been observed [49], with the so called Prandtl number P φ = χ φ /χ i ≈ 1 relating ion momentum and ion energy diffusivity. This is consistent with theoretical studies of ITG transport.…”
Section: Momentum Confinementmentioning
confidence: 99%
“…Modulation at a suitable frequency has the advantage of optimizing the S/N ratio by averaging over several cycles and has been used successfully to study electron and more recently ion heat transport, and also particle and impurity transport (see [18] for a recent review). Its application to momentum transport studies using Neutral Beam Injection (NBI) modulation is a recent development, with a couple of studies reported in JT-60U [19,20], one experiment reported in JET [21,22,23] and one in DIII-D [24]. The use of magnetic perturbations to brake the plasma was reported in DIII-D [25] and NSTX [24,26,27] as another means to induce a transient from which it is possible to infer diffusivity and convection separately.…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes momentum perturbative experiments using Neutral Beam Injection (NBI) modulation at JET, presenting both new experiments and more refined analysis and modelling with respect to previous work [21,22,23] and including detailed comparison of the results with recent gyro-kinetic and fluid theory predictions. Sect.2 illustrates the experiments, Sect.3 discusses the calculations of the time dependent torque deposition, Sect.4 illustrates the rather heavy experimental methodology, based on transport modelling required to extract from the data the estimates of momentum diffusivity and pinch, Sect.5 summarizes the linear gyro-kinetic predictions, Sect.6 describes first attempts to perform time-dependent modelling of the rotation dynamic response with 1D quasilinear fluid transport models.…”
Section: Introductionmentioning
confidence: 99%